Multifocal atherosclerosis in patient after acute first degree radiation sickness. - Metlyaeva N.A.; Lartsev M.A.; Shcherbatykh O.V.; Bushmanov A.Yu.; Krasnyuk V.I. (Саратовский научно-медицинский журнал, 2014)
Purpose: assessment the heavy psychosomatic and all-somatic cardiovascular and cerebrovascular pathology of patient, transferred an acute I degree radiation sickness, from the general evenly gamma-beta radiation. Conclusions. The subdepressive and disturbing-depressive syndrome of patient, transferred an acute radiation sickness (ARS) of I degree, from the general evenly gamma-beta radiation, was independent risk factor of development of multifocal atherosclerosis; Features of development of all-somatic and psychosomatic pathology of patient are based on a combination of genetic prerequisites, environment influences (the stress caused by accident on the ChNPP) and social factors, influencing on him during a course of life, especially during early socialization. Thus at development of psychosomatic frustration the combination of feature of the mental reaction connected with the personal characteristic and special relationship between mental (stress) and physiological (somatic) by aspects of reaction which led to metabolism violation, to aging, decrease in adaptation opportunities of an organism and development age — dependent pathology took place.